2013 IEEE International Ultrasonics Symposium (IUS) 2013
DOI: 10.1109/ultsym.2013.0532
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of bone thickness and velocity for ultrasonic computed tomography using transmission-echo method

Abstract: International audienceThe robustness and accuracy of the transmissionecho (TE) method is investigated on simultaneous thickness and velocity estimation of double-layered thin bone samples. Twentytwo pairs of bovine cortical samples were assembled and measured by two pairs of immersion transducers with nominal frequencies of 1MHz and 2.25MHz. For each measurement, the TOF of six pulses contained by one transmission and two echo signals were detected and then used for the calculation. The mean relative errors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…for soft tissue at 2MHz was about 1dB/cm (Kremkau, 2002); the difference of the soft tissue thickness among subjects was usually only a few millimeters (Vermess et al, 2012;Zheng and Lasaygues, 2013), and it demonstrated that the attenuation caused by soft tissue was mostly less than 1dB for pediatrics.…”
Section: Frequency Amplitude Index (Fai)mentioning
confidence: 99%
“…for soft tissue at 2MHz was about 1dB/cm (Kremkau, 2002); the difference of the soft tissue thickness among subjects was usually only a few millimeters (Vermess et al, 2012;Zheng and Lasaygues, 2013), and it demonstrated that the attenuation caused by soft tissue was mostly less than 1dB for pediatrics.…”
Section: Frequency Amplitude Index (Fai)mentioning
confidence: 99%
“…Measuring bone SOS and cortical shell thickness using transmitted and reflected pulses has been proposed by Zheng and Lasaygues (2013) using single-element transducers at a single angle. It is extended here using reconstructed PE-UCT and T-UCT data instead of the raw echo data.…”
Section: Theorymentioning
confidence: 99%
“…(1) to merge temperature information with others [5] specially with 3D exams which represent the same patient like magnetic resonance, (2) to represent a model of the breast with a 3D mesh for surgical reconstruction after mastectomy modeling, (3) to identify points of correlation between IR exams and models of the patient body for finite elements analysis or other forms of treatment of the inverse problem (i.e., what is inside of the body that can result in a thermal distribution of skin' surface) [3,11,24] and (4) for some numerical analysis and other examinations like Electrical Impedance Tomography (EIT) [14] and 3D Ultrasound [35]. Moreover, three dimensional meshes of the real model can be used in surgeries simulations, for the personal project of prosthesis, for breast reduction, and other procedures.…”
Section: Three-dimensional Reconstructionmentioning
confidence: 99%